The Prevalence and Causes of Visual Impairment and Blindness Among Older Adults in the City of Lodz, Poland. Issue 5 (February 2015) - Nowak, Michal S.; Smigielski, Janusz
Abstract : Abstract: To investigate the prevalence and causes of visual impairment and blindness in a sample of Polish older adults. The study was designed in a cross-sectional and observational manner. Data concerning the vision status were assessed in 2214 eyes from 1107 subjects of European Caucasian origin; most of whom live in the city of Lodz, in central Poland. Visual impairment was defined as distance visual acuity <20/40 in the worse-seeing eye. Low vision was defined as best-corrected visual acuity (BCVA) <20/40 but >20/200 in better-seeing eye, and blindness was defined as BCVA ⩽20/200 in both eyes (United States criteria). Visual impairment was found in 27.5% subjects in the worse-seeing eye. Multiple regression analysis showed that increasing age (OR 0.98, 95% CI 0.97–0.99) and female gender (OR 1.47, 95% CI 1.11–1.93) were independent risk factors. No association was found between visual impairment and socioeconomic status of subjects. Noncorrectable visual impairment was found in 7.0% of subjects, including 5.2% of subjects with unilateral and 1.8% of subjects with bilateral visual impairment. Low vision and blindness accounted for 1.3% and 0.5%, respectively, and were only associated with older age (OR 1.05, 95% CI 1.02–1.10). Retinal diseases represented the major cause of noncorrectable visual impairment and accounted for more than half of causes of blindness. Provision of appropriate refractive correction improves visual acuity in 75% subjects presenting with visual impairment. Retinal diseases are a major cause of noncorrectable visual impairment and blindness in this older population.